Pelatihan Penggunaan Microsoft Office Dalam Guna Meningkatkan Ketrampilan Dan Keahlian Kepada Para Siswa/i PKBM Penerus Bangsa Tangerang Selatan - Akrom; Aniq Astofa; Zainudin (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Education is an  important activity role in the development and changes that will occur in society. In today's era, competition for jobs is becoming increasingly fierce. To face this fierce competition in the world of work, students are expected to have skills, one of which is the use of Microsoft Office. PKBM Penerus Bangsa Tangerang Selatan aims to enhance students' skills in using the widely used software Microsoft Office Excel. Microsoft Office Excel is one of the most renowned software programs globally. To use Microsoft Office Excel effectively, students must master its techniques. Therefore, to assist our students, the PKM Dosen Universitas Pamulang team will conduct training and workshops titled “Training on the Use of Microsoft Office to Enhance Skills and Competencies for Students of PKBM Penerus Bangsa Tangerang Selatan”.